The association between parental socio-economic level and dental caries in 12-year-old children - Heriasti, Maudina Dwi; Susilawati, Sri; Suwargiani, Anne Agustina (Padjadjaran Journal of Dentistry, 2015)
Introduction: Dental caries is among the most prevalent chronic diseases affecting children globally. It results from the demineralization of tooth structures due to the complex interaction of various factors, including diet, oral hygiene, and bacterial activity. Socioeconomic status (SES) is a well-established determinant of health that influences access to healthcare services, education, and health-related behaviors. Children from lower socioeconomic backgrounds are generally at greater risk of developing dental caries due to limited access to preventive care and reduced awareness of oral hygiene practices. This study examines the association between parental socioeconomic status—encompassing education, occupation, and income—and the prevalence of dental caries among 12-year-old children in Pangkalan Jati, Depok City, Indonesia. Methods: A descriptive cross-sectional study was conducted involving 111 twelve-year-old children, selected through total sampling. Dental caries status was evaluated using the DMF-T index (Decayed, Missing, Filled Teeth). Data on parental education, occupation, and household income were collected and analyzed for correlation with children’s DMF-T scores. Results: The mean DMF-T score among participants was 2.8, indicating a moderate caries severity according to WHO criteria. Significant inverse correlations were found between DMF-T scores and paternal education (rₛ = -0.383, p < 0.001), maternal education (rₛ = -0.278, p = 0.003), paternal occupation (rₛ = -0.377, p < 0.001), and household income (rₛ = -0.335, p < 0.001). No significant correlation was observed with maternal occupation (rₛ = -0.138, p = 0.150). Conclusion: Parental socioeconomic status—particularly education, occupation, and income—significantly influences the prevalence of dental caries among children. These findings underscore the importance of implementing targeted oral health education and intervention programs for socioeconomically disadvantaged families.